Comparative rentals - Courter, Forrest Leslie (My University, 1905)
Introduction: The state of Kansas, lyingas it does with its eastern border along the Missouri River, and its gradually elevated area extending westward for a distance of 400 miles, affords an interesting study for this subject. I said "gradually elevating," and this is true because the streams which have farmed the broad, fertile valley of the eastern portion are the sum of the many small streams which drain the western counties. We find that prices of land vary according to the location, and this variation in price is also largely in accord with the yield of cross. The price of land also regulates the rental of land. Land rental varies somewhat in a series of years, but its variation has rather been a gradual increase, correspondent to the rise the price of land during the last few years. In eking a comparison in the rental values of land in Kansas, the statistics in the 13th and 14th biennial reports of the State Board of Agriculture have been used as the foundation. Since these statistics are those given in by the assessors of the several townships, they are doubtless as complete and reliable statistics as can be obtained. It would be exceedingly difficult and doubtless nee6. Less to consider the statistics of every county, therefore, it is seemed best to take certain counties that are so located that their statistics shall be indicative of that section of the state, and make a comparison of these. I have chosen two 77estern, two Central, and two Eastern counties. I have selected as one of the western counties, Logan County. It is the second county from the Colorado line and in the third tier of counties from the north. Though all this section is considered high land, this county is no more so than other counties, for the Smoky Kill river flows through it. The other ' western county that T shall consider is Ford County. It is second from the South and fifth from the Colorado line. This county includes a portion of the Arkansas valley and is therefore indicative of that section of the state.
Citation: Courter, Forrest Leslie. Comparative rentals. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Comparison of Kansas Counties; Cloud County; Solomon County; Theses